2018
DOI: 10.1371/journal.pone.0207203
|View full text |Cite|
|
Sign up to set email alerts
|

Risk factors associated with prolonged hospital length-of-stay: 18-year retrospective study of hospitalizations in a tertiary healthcare center in Mexico

Abstract: BackgroundHospital length-of-Stay has been traditionally used as a surrogate to evaluate healthcare efficiency, as well as hospital resource utilization. Prolonged Length-of-stay (PLOS) is associated with increased mortality and other poor outcomes. Additionally, these patients represent a significant economic problem on public health systems and their families. We sought to describe and compare characteristics of patients with Normal hospital Length-of-Stay (NLOS) and PLOS to identify sociodemographic and dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
74
2
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(82 citation statements)
references
References 22 publications
4
74
2
2
Order By: Relevance
“…Using the same definition for prolonged hospitalization, O’Sullivan et al conducted a single-centre study within the same jurisdiction as our study and similarly found that 13.1% of hospital admissions were at least 14 days, but used 49.1% of bed days [ 44 ]. Marfil-Garza et al conducted a single-centre study in Mexico and found that 5.1% of admissions had a LOS more than 34 days but used 23.1% of total bed days [ 42 ]. Among general medicine discharges, Anderson et al revealed that 2.3% of discharges were longer than 21 days, but accounted for 18.6% of total inpatient days [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the same definition for prolonged hospitalization, O’Sullivan et al conducted a single-centre study within the same jurisdiction as our study and similarly found that 13.1% of hospital admissions were at least 14 days, but used 49.1% of bed days [ 44 ]. Marfil-Garza et al conducted a single-centre study in Mexico and found that 5.1% of admissions had a LOS more than 34 days but used 23.1% of total bed days [ 42 ]. Among general medicine discharges, Anderson et al revealed that 2.3% of discharges were longer than 21 days, but accounted for 18.6% of total inpatient days [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have identified factors associated with protracted hospitalization, but many of these have focused on targeted patient populations [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ] or involved data collected at a single centre [ 13 , 18 , 19 , 23 , 24 , 28 , 29 , 31 , 37 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ] Understanding the factors that contribute to prolonged hospitalization in a broader patient cohort may guide the development of interventions that target at risk patients, improve overall care, and reduce resource utilisation.…”
Section: Introductionmentioning
confidence: 99%
“…However, in a retrospective study at a single tertiary health care center in Mexico, young people, male sex, a lower physician-to-patients rate, weekend hospitalization, presence of surgery, number of complications, residence outside the city and lower socioeconomic status were associated with prolonged hospitalization. 29 According to a WHO (world health organization) report, there were 4.9 million deaths by injury in 2016, of which 1.4 million patients died in road accidents worldwide, three quarters of whom were men or boys. 30 As this study was conducted in a developed country, the differences in health and medical situations in developed and developing countries may affect the results.…”
Section: Discussionmentioning
confidence: 99%
“…The duration of hospitalization may re ect the severity of diseases, complications rates, and medical costs. Furthermore, studies in geriatric and general populations indicate that prolonged hospitalization is associated with increased functional dependence, infection, and comorbidities [18][19][20].…”
Section: Spot Sign Surgery and Length Of Hospital Staymentioning
confidence: 99%